THE ROLE OF LEADERSHIP IN SECONDARY SCHOOLS WITHIN - Sito, Paul Pule (My University, 2011)
The interplay between management and leadership significantly affects the successful implementation of public policies. Public managers sometimes overmanage their institutions, while under-leading them. A consequence of traditional authoritarian management can be demoralised and unmotivated personnel bent only on job-retention and unconcerned about service delivery. This study focused on how school managers in Tshwane West interacted with their environment to deliver quality education. The practices in well-performing schools in the township were observed and compared with those in less successful schools. Many principals were found to be confused about the difference between the concepts of leadership and management. They extensively relied on outdated management principles. Schools were mostly not using their avowed visions for the future as their focal point. But they were nevertheless anxious to produce good annual matriculation results. It was found that school leadership would benefits from empowering its employees. Some basic management principles are required to ensure accountability, especially with how budget is spent. But to render quality service, employees need to experience ownership of their environment. Largely informal, but far-reaching and sustainable leadership practices can facilitate this state of affairs
MM - P&DM
Keywords: Leadership; Schools and schooling